Pengembangan Model Pembelajaran Quantum Teaching Tipe Tandur untuk Meningkatkan Minat Belajar Siswa - Leni Damayanti; Erliany Syaodih; Anytha Basaria Silitonga (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2015)
This research is motivated by the lack of student interest in learning economy. Students who are interested in learning tend to be happy, interested in everything they are facing, caring about, and wanting to be involved in the PBM's activities. The efforts of teachers in implementing the learning activities currently not oriented to increase student interest. Based on these problems, it needs to be an innovation in learning which aims to find a suitable learning model to increase student interest is quantum teaching learning model types TANDUR combined with Mind Mapping method. The method used in this study is a research and development (Research and Development) including the use of descriptive models and action research. The implementation of the R & D method is divided into three steps: preliminary study, development and testing. The population used is class X in SMA Negeri 11 Bandung. Sampling for testing using purposive sampling with particular consideration is based on the advice of teachers of economic subjects the sample used during the limited test is class X-MIA5 whereas at the time of extensive testing is a class X-IIS1 as experimental class and class X-IIS3 as the control class by using Quasi-Experimental Design of Matching pretest-posttest control group design. Based on the results of data processing, it can be concluded that the development of quantum learning model is more effective TANDUR type used in the learning economy in increasing student interest compared with the learning model.